Halitosis: Much beyond oral malodor - Ongole, R; Shenoy, N (Kathmandu University Medical Journal, 2010)
Oral malodor one of the most common complaints with which patients approaches us thinking it can be detrimental to his self-image and confidence. Even though majority of oral malodor is of oral origin, there are multiple other systemic causes that have to be addressed while we diagnose and treat this condition. Most of these patients look up to oral care physicians for expert advice, it is critical for us to have the knowledge base and communication techniques to provide quality clinical assessment and implement effective intervention programs. This article reviews the various causes and the diagnostic modalities which will help us treat this multifaceted condition. Key words: Halitosis; Oral malodor; Systemic diseases; Diagnosis DOI: 10.3126/kumj.v8i2.3574 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 269-275